Giordano Bruno : an introduction - Blum, Paul Richard. (Value Inquiry Book Series, 2012)
Giordano Bruno (1548-1600) was a philosopher in his own right. However, he was famous through the centuries due to his execution as a heretic. His pronouncements against teachings of the Catholic Church, his defence of the cosmology of Nicholas Copernicus, and his provocative personality, all this made him a paradigmatic figure of modernity. Bruno's way of philosophizing is not looking for outright solutions but rather for the depth of the problems; he knows his predecessors and their strategies as well as their weaknesses, which he exposes satirically. This introduction helps to identify the original thought of Bruno who proudly said about himself: "Philosophy is my profession!" His major achievements concern the creativity of the human mind studied through the theory of memory, the infinity of the world, and the discovery of atomism for modernity. He never held a permanent office within or without the academic world. Therefore, the way of thinking of this "Knight Errant of Philosophy" will be presented along the stations of his journey through Western Europe.